Quantitative method of viral pollution determination for large volume of water using ferric hydroxide gel impregnated on the surface of glassfibre cartridge - Akira Homma; Hermann G. Schatzmayr (Memorias do Instituto Oswaldo Cruz, 1974)
Quantitative method of viral pollution determination for large volume of water using ferric hydroxide gel impregnated on the surface of glassfibre cartridge filter. The use of ferric hydroxide gel, impregnated on the surface of glassfibre cartridge filter enable us to recover 62.5% of virus (Poliomylitis type I, Lsc strain) exsogeneously added to 400 liters of tap-water. The virus concentrator system consists of four cartridge filters, in which the three first one are clarifiers, where the contaminants are removed physically, without significant virus loss at this stage. The last cartridge filter is impregnated with ferric hydroxide gel, where the virus is adsorbed. After the required volume of water has been processed, the last filter is removed from the system and the viruses are recovered from the gel, using 1 liter of glycine/NaOH buffer, at pH 11. Immediately the eluate is clarified through series of cellulose acetate membranes mounted in a 142mm Millipore filter. For the second step of virus concentration, HC1 1N is added slowly to the eluate to achieve pH 3.5-4. MgC1, is added to give a final concentration of 0.05M and the viruses are readsorbed on a 0.45 , porosity (HA) cellulose acetate membrane, mounted in a 90 mm Millipore filter. The viruses are recovered using the same eluent plus 10% of fetal calf serum, to a final volume of 3 ml. In this way, it was possible to concentrate virus from 400 liters of tap-water, into 1 liter in the first stage of virus concentration and just to 3 ml of final volume in a second step. The efficiency, simplicity and low operational cost, provded by the method, make it feasible to study viral pollution of recreational and tap-water sources. Relata-se o emprego de um concentrador portátil, o qual se mostrou capaz de recuperar 62,5% dos vírus (Polio I, amostra Lsc) experimentalmente dispersos em 400 litros de água, os quais foram reduzidos a 3 ml. O sistema concentrador de vírus é composto de quatro filtros-bobina, em que os três primeiros são clarificadores de porosidade decrescente e não retentores de partículas, e o último, impregnado com gel de hidróxido de ferro, adsorvedor das partículas virais presentes na água processada. Este quarto filtro, é removido do sistema após o processamento inicial da água. Em seguida, ainda ana primeira fase de concentração, os vírus são eluídos do filtro-bobina, com solução de glicina /NaOH, pH 11,0. Subseqüentemente, o eluato é reclarificado, sem redução de volume, por filtração através membranas de acetato de celulose (15 µm, 1,2 µm, 0,45 µm e 0,22 µm) montadas em série, em um suporte Millipore de 142 mm de diâmetro. Para a segunda etapa de concentração, ajusta-se o eluato clarificado a pH 3,5 e adiciona-se cloreto de magnésio até a concentração final de 0,05M. Os vírus são a seguir adsorvidos em membranas de acetato de celulose, de porosidade 0,45 µm, em filtro Millipore de 90mm de diâmetro, novamente recuperados por trituração da membrana em gral de vidro, em presença de 3 ml do tampão glicina / NaOH, nesta fase porém, suplementado com 10% de soro bovino fetal. Desse modo foi possível concentrar vírus, de 400 litros de água para 1 litro na primeira etapa e apenas 3 ml de volume final na segunda etapa. A eficiência, a simplicidade e o baixo custo operacional do método recomenda-os pata o estudo da poluição viral de águas recreacionais e fontes supridoras de água potável.